Efeitos da terapia de restrição e indução ao movimento (TRIM) no tempo de execução das tarefas pós-AVC: um estudo de caso - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2023)
Introduction: Stroke is a cerebrovascular disease typically caused by the rupture or obstruction of blood vessels in the brain and that affects millions of people every year and is considered one of the main causes of death and disability worldwide. RTMI is a training method that aims to restore the motor function of patients affected by this pathology and that demonstrates positive results in its applications. Objective: To analyze the effects of RTMI on task execution time after stroke sequelae. Methodology: This is a cross-sectional case study, carried out with an individual, 62 years old, with a clinical diagnosis of ischemic stroke, 2 years ago. The evaluation instruments and measures were: Motor function (Wolf Motor Function Test - WMFT) and Motor activity (Motor Activity Log - MAL) and evaluation of the execution time of the shaping tasks. Results: The participant who received the protocol proposed in this study showed a reduction in the execution time of the tasks in relation to the average time it took to complete the tasks in each meeting, from 17.17 seconds to 10.19 seconds on odd days on the last day. While on even days it went from 14.02 to 12.30 seconds. With the reduction in the execution time on odd days, 3 shaping tasks were included without compromising the engagement and execution of the tasks Conclusion: it is concluded that RTMI showed promising results in relation to the reduction in the execution time of tasks involving the use of the upper limb in the investigated participant.
Keywords: Acidente vascular cerebral; Reabilitação; Terapia por exercício; CNPQ::CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; ODS 3 – Saúde e bem-estar